DESIGN AND DEVELOPMENT OF GAME ASSETS " GUERRILLA WARFARE OF GENERAL SUDIRMAN" WITH 2D PIXEL ART CONCEPT - Heru Wijayanto Aripradono; Defryn Fratelry Willim (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Indonesia has a lot of history and heroic stories from Indonesian heroes who have fallen. However, as time goes by, not many people know the stories of their heroism, especially among young people such as children and teenagers. Games can be a medium of learning to recognize letters and numbers, shapes, colors and even to get to know history. An attractive game design can be an attraction for players to play it, especially among children to teenagers. This refers to the importance of digital art design as a support for game-based learning media. Pixel art for games can look beautiful even if it's simple. In addition, pixel art can also be a characteristic of games that are increasingly popular with the public, so that being created by game developers today in a pixel art style, it is an experience offered by modern game developers to gamers. By combining some of these concepts, finally emphasizing this application study by creating a game asset design with the genre of Indonesian heroes' history with the concept of 2d pixel art as a medium for learning history for young students in Indonesia. This research uses the PDDIE development method (Planning, Design, Development, Implementation, Evaluation). This design method is used as the output of this research in the form of designing the "asset" of the General Sudirman Guerrilla War game using the concept of 2D pixel art.